2016
DOI: 10.6002/ect.2016.0290
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Since the first successful organ transplant conducted between twins in 1954, kidney transplant has evolved considerably over the past 50 years. Kidney transplant plays an important role in the treatment of end-stage kidney disease to improve the quality of life and prolong the life of patients. Despite significant advances, postoperative medical and surgical complications still represent important causes of morbidity and mortality. Many problems can be avoided through prophylactic correction of abnormalities d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Study limitations include the small sample size, which limits our ability to determine significant risk factors for the development of postoperative complications, and the lack of a comparison group comprised of similar grafts but without the requirement for PN. However, as described above, data from previous studies have shown similar incidences of urologic complications ( 35 , 37 ) and surgical complications ( 38 , 39 ), as well as similar clinical outcomes ( 40 ).…”
Section: Discussionmentioning
confidence: 53%
“…Study limitations include the small sample size, which limits our ability to determine significant risk factors for the development of postoperative complications, and the lack of a comparison group comprised of similar grafts but without the requirement for PN. However, as described above, data from previous studies have shown similar incidences of urologic complications ( 35 , 37 ) and surgical complications ( 38 , 39 ), as well as similar clinical outcomes ( 40 ).…”
Section: Discussionmentioning
confidence: 53%
“…In the first 24 hours after kidney transplantation, nursing actions aim to prevent complications and prioritize the continuous evaluation of general health status with noninvasive monitoring of vital signs and evaluation of the nursing team of 1 hour/1 hour in the first 12 postoperative hours, which allows early and appropriate interventions for each type of worsening. This period of great potential for hemodynamic instability, cardiovascular and neurological complications, important metabolic alterations and the need for replacement of parenteral fluids in large volumes that require intensive care for the maintenance of life (5,23,43,(44)(45)(46)(47)(48)(49).…”
Section: Resultsmentioning
confidence: 99%
“…MUCs are the most common pathology after KT and are related to significant morbidity and mortality. 19 New surgical techniques have decreased the incidence of MUCs. 8 We analyzed a cohort of 1584 KT and determined its MUCs incidence, risk factors and their influence with graft loss and KT recipients’ mortality.…”
Section: Discussionmentioning
confidence: 99%